Study on Traditional Technology of Nepalese Fried Snack Woh - Adhikari, Bhaskar Mani; Dangol, Karishma (Journal of Food Science and Technology Nepal, 2014)
Woh is a deep oil fried spongy Nepalese indigenous product. This work was done to find out the basics of woh and to prepare best from different formulations using unlike particle size and different frying media. Green gram and black gram in a ratio of 100:0, 50:50, 60:40, and 70:30 were mixed and ground on stone grinder and mixer grinder for different particle sizes. Batter mixed with spices were whipped and deep fried in mustard, soybean and sunflower oil separately at 204 ± 2ºC for 2.5 ± 0.5 minutes. Woh with 60:40 combination having 103 μm particle size fried in soybean oil was found to be nutritious with less oil uptake and less anti nutritional factors. DOI: http://dx.doi.org/10.3126/jfstn.v8i0.11747 J. Food Sci. Technol. Nepal, Vol. 8 (35-39), 2013